Pengaruh Kecerdasan Emosionald dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Bank BTN Cabang Maros - Nurmega Nurmega (Jurnal Online Manajemen ELPEI, 2021)
The purpose of this study was to determine emotional intelligence and work motivation on employee performance at Bank BTN Maros Branch, while this study was analyzed using quantitative analysis, namely multiple linear regression analysis. based on the results of the research above regarding the effect of emotional intelligence on performance, the authors conclude that the influence of emotional intelligence does not affect employee performance at the Maros branch of Bank BTN. Based on the simple linear regression test, the employee performance coefficient value is 0.279. Stating that every time there is an increase of 1 score for emotional intelligence will be followed by an increase in employee performance of 0.279.